Impact of artificial intelligence on branding: a bibliometric review and future research directions - Truong Thi Hue; Ta Huy Hung (Humanities & Social Sciences Communications)
Abstract The rapid development of Artificial Intelligence (AI) is significantly transforming the branding strategies of organisations, attracting considerable attention from scholars and practitioners worldwide. This study aims to explore the volume and growth trajectory, geographic contributions, influential authors, prominent documents, main schools of thought, and future research directions on the impact of AI on branding. The PRISMA guidelines are used to identify 592 eligible documents indexed in Scopus from 1982 to 2023. Bibliometric method with descriptive statistics and scientific mapping are conducted. The study reveals a significant increase in publications in the field over the past four decades, peaking in 2023. The United States, the United Kingdom, and India are the leading countries in this field. Six main schools of thought are identified, and five directions for future research are proposed. The most influential authors and documents are also highlighted. This is one of the few studies that review the impact of AI on branding and is likely the first to use Scopus data up to 2023.